Mortality risk disparities in children receiving chronic renal replacement therapy for the treatment of end-stage renal disease across Europe: an ESPN-ERA/EDTA registry analysis - Chesnaye, Nicholas; Schaefer, Franz (The lancet, 2017)
Summary Background We explored the variation in country mortality rates in the paediatric population receiving renal replacement therapy across Europe, and estimated how much of this variation could be explained by patient-level and country-level factors.Methods In this registry analysis, we extracted patient data from the European Society for Paediatric Nephrology/European Renal Association-European Dialysis and Transplant Association (ESPN/ERA-EDTA) Registry for 32 European countries. We included incident patients younger than 19 years receiving renal replacement therapy. Adjusted hazard ratios (aHR) and the explained variation were modelled for patient-level and country-level factors with multilevel Cox regression. The primary outcome studied was all-cause mortality while on renal replacement therapy.Findings Between Jan 1, 2000, and Dec 31, 2013, the overall 5 year renal replacement therapy mortality rate was 15·8 deaths per 1000 patient-years (IQR 6·4-16·4). France had a mortality rate (9·2) of more than 3 SDs better, and Russia (35·2), Poland (39·9), Romania (47·4), and Bulgaria (68·6) had mortality rates more than 3 SDs worse than the European average. Public health expenditure was inversely associated with mortality risk (per SD increase, aHR 0·69, 95% CI 0·52-0·91) and explained 67% of the variation in renal replacement therapy mortality rates between countries. Child mortality rates showed a significant association with renal replacement therapy mortality, albeit mediated by macroeconomics (eg, neonatal mortality reduced from 1·31 [95% CI 1·13-1·53], p=0·0005, to 1·21 [0·97-1·51], p=0·10). After accounting for country distributions of patient age, the variation in renal replacement therapy mortality rates between countries increased by 21%.Interpretation Substantial international variation exists in paediatric renal replacement therapy mortality rates across Europe, most of which was explained by disparities in public health expenditure, which seems to limit the availability and quality of paediatric renal care. Differences between countries in their ability to accept and treat the youngest patients, who are the most complex and costly to treat, form an important source of disparity within this population. Our findings can be used by policy makers and health-care providers to explore potential strategies to help reduce these health disparities.Funding ERA-EDTA and ESPN.
Available online 20 March 2017
Gesehen am 05.07.2018